2019
DOI: 10.2478/eko-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the selected remediation medium on the cadmium bioavailability in the selected ecosystem in the Southwestern locality of Slovakia

Abstract: Soil is a sensitive ecological factor. Biodegradable materials from the environment can also be used to deal with serious ecological problems. Soil affecting by remediation medium - garden compost - was analysed for toxic cadmium (Cd) in terms of environmental protection. The objective of this research was to analyse soil and compost at foothill locality of the Tribeč Mountains (Southwestern Slovakia) in the years 2015−2017 to determine Cd contents in soil and compost, pH and to assess Cd bioavailability. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The availability of macronutrients and micronutrients, such as Zn, also affect Cd's absorption in plants [147]. Cadmium slows down the root system's growth and causes chlorosis, even necrosis, with an overall decrease in biomass and yields [26]. We have reached similar results in our research as well.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The availability of macronutrients and micronutrients, such as Zn, also affect Cd's absorption in plants [147]. Cadmium slows down the root system's growth and causes chlorosis, even necrosis, with an overall decrease in biomass and yields [26]. We have reached similar results in our research as well.…”
Section: Discussionsupporting
confidence: 83%
“…Factors affecting the process of soil contamination and thus sustainable agriculture are, for example: human activity, the organic carbon content in the soil, pH, available phosphorus, soil structure, and the capacity of exchangeable cations [19][20][21][22][23]. Soil contamination can damage and cause deterioration of water quality and have a negative impact on the environment [24][25][26]. Many studies have found that land-use change [27], cultivated plants, surrounding transport networks and hydrology of the territory [28,29], diversity of land use [30], and different ways of maintaining the soil are related to soil contamination [27][28][29][30][31][32][33].…”
Section: Heavy Metals In Soil-plant Systemsmentioning
confidence: 99%
“…Numerous studies confirmed that revegetation is the most efficient, effective and widely accepted way to environmental stabilization of waste rock dumps in post-mining areas. The scholars and experts indicated that a sustainable vegetation cover can cause many positive on the dumps (de Lima, Mendanha, 2019; Zverkovskyy et al, 2018;Zhukov et al, 2021;Urminska et al, 2019). But, the practical application of revegetation techniques is very difficult for the following reasons: (i) high cost of the implementation; (ii) long-term preparation and (iii) potential limitations of material availability (Lacy, 2019;Raizada, Dhyani, 2020;Stanturf et al, 2021;Vriens et al, 2020).…”
Section: Assessment Of Heavy Metals Concentration In Initial Soils Of...mentioning
confidence: 99%
“…Numerous researchers have convincingly proven that waste rock dumps have a strong and negative impact on the environment. Moreover, in many countries, especially in developing countries, environmental, social and stabilization issues have not been considered as an integral part in mining (Fazekas et al, 2018;Savosko et al, 2020bSavosko et al, , 2021Sediva, Izakovicova, 2015;Urminska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%